An experimentally-verified approach for enhancing fluid drag force simulation in vertical oilwell drill strings. Issue 1 (31st December 2022) - Galagedarage Don, Mihiran; Rideout, Geoff
ABSTRACT: The oilwell drilling fluid flows cause viscous and hydrodynamic forces on drill strings. This effect is ignored or treated as a constant in most drill string models. The present study introduces mathematical models for lateral vibration damping and axial drag forces that are employable in lumped segment drill string models. First, the variables to which drilling fluid-generated forces are most sensitive were identified and the Response Surface Method was applied to design the experiment matrix. The lateral vibration-damping experiments, which were validated using a scaled-down physical model, and the axial drag experiments were done using Fluid-Structure Interaction simulations. The results were statistically analysed to acquire the models and were implemented in a 3D lumped segment bond graph developed using the Newton-Euler formulation and body-fixed coordinates. The results indicate a considerable effect of the extended treatment of damping and axial drag on bending moment fluctuation, wellbore interactions, and weight on bit.